2021
DOI: 10.3390/md19050236
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of Chitosan Degradation in Organic Acid Solutions

Abstract: This paper presents a comparative study on chitosan degradation in organic acid solutions according to their different dissociation characteristics. More precisely, the aim of the study was to determine the kinetics of the degradation process depending on the different acid dissociation constants (pKa values). The scientists involved in chitosan to date have focused mainly on acetic acid solutions. Solutions of lactic, acetic, malic, and formic acids in concentrations of 3% wt. were used in this research. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…13 In this condition, the hydroxyl (OH − ) ions react with acetamide groups and generate a dianion intermediate species which converts into chitosan. 14 The structure of chitosan consists of randomly distributed β-(1→4)-N-acetyl-D-glucosamine and β-(1→4)-D-glucosamine residues. 12…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 In this condition, the hydroxyl (OH − ) ions react with acetamide groups and generate a dianion intermediate species which converts into chitosan. 14 The structure of chitosan consists of randomly distributed β-(1→4)-N-acetyl-D-glucosamine and β-(1→4)-D-glucosamine residues. 12…”
Section: Introductionmentioning
confidence: 99%
“…13 In this condition, the hydroxyl (OH À ) ions react with acetamide groups and generate a dianion intermediate species which converts into chitosan. 14 The structure of chitosan consists of randomly distributed β-(1→4)-N-acetyl-D-glucosamine and β-(1→4)-D-glucosamine residues. 12 Although the deacetylation reaction can be controlled by several parameters, the conversion from acetyl to amine groups is difficult to complete, and repetitive deacetylation is often required in order to achieve high conversion from chitin to chitosan.…”
Section: Introductionmentioning
confidence: 99%
“…At one day after solution preparation, η 0 = 540 ± 30 Pa.s, and four days after solution preparation, η 0 = 320 ± 10 Pa.s, representing a reduction of approximately 40.7%. The drop in viscosity can be attributed to the degradation of the chitosan by hydrolysis, which occurs mainly under the influence of acids [ 24 , 25 ], such as acetic acid, affecting the degree of degradation and the molecular mass of oligochitosan [ 26 ]. Similarly, in Fig 2B the frequency sweep showed that the storage and loss moduli of the solution, which represent a measure of elastic and viscous response of a material, respectively, were lower when comparing both time points, one versus four days.…”
Section: Resultsmentioning
confidence: 99%
“…At one day after solution preparation, η 0 = 540 ± 30 Pa.s, and four days after solution preparation, η 0 = 320 ± 10 Pa.s, representing a reduction of approximately 40.7%. The drop in viscosity can be attributed to the degradation of the chitosan by hydrolysis, which occurs mainly under the influence of acids [24,25], such as acetic acid, affecting the degree of degradation and the molecular mass of oligochitosan [26].…”
Section: Stability Analysis and Reuse Capability Of The Chitosan Solu...mentioning
confidence: 99%
“…It is highly probable that the rate of CS degradation is mainly determined by the presence of acid in the environment and only by other factors such as concentration and molecular weight. The presence of acid in CS materials mainly causes the hydrolysis of the polymer to lower molecular weight without significantly affecting the degree of deacetylation and polydispersity [ 22 ]. We observed a similar phenomenon during the attempt to thermally degrade dry CS-poly(vinyl acid) composites, in which the elimination of the acid from the CS material significantly increases its stability during thermal treatment, even when it is used as a filler for thermoplastic materials [ 1 ].…”
Section: Resultsmentioning
confidence: 99%